Trio albums for violin, violoncello and piano Violoncello part - ALBENIZ [et.al.] (The Boston Music Co., 1916)
Tango in dnMinuetnBy the BrooknPrelude in A-flatnPassepiednSerenadenTold at TwilightnValzer gentilenInterlude orientalnElegy